Comparison of Platelet-Rich Plasma with Corticosteroid Injections for Patients with Mild to Moderate Carpal Tunnel Syndrome: A Systematic Review and Meta-Analysis of Current Evidence in Randomized Controlled Trials - I Made Wira Kusuma; Made Bramantya Karna; Anak Agung Gde Yuda Asmara; Stedi Adnyana Christian (Indonesian Journal of Global Health Research, 2024)
Carpal tunnel syndrome (CTS) accounts for over 90% of peripheral entrapment neuropathy cases. Platelet-rich plasma (PRP), has shown promise due to its anti-inflammatory effects and potential to support axonal repair and neuronal regeneration. The aim of this study is to evaluate the comparative therapeutic efficacy of PRP and corticosteroid injections in treating mild to severe CTS, using a three-month follow-up period.Methods: This meta-analysis followed the PRISMA framework, reviewing studies from 2017 to 2022 in PubMed and the Cochrane Library that compare PRP and corticosteroid injections for CTS. Primary outcome including Visual Analog Scale (VAS), Sensory Peak Latency (SPL), Distal Motor Latency (DML), and the Boston Carpal Tunnel Questionnaire Symptom Severity Scale (BCTQ-SSS). Results: Four studies remained after matches the screening phase. This meta-analysis includes 245 patients, including 123 receiving PRP and 122 corticosteroid injections. When looking at the VAS 1 and 3 month periods, FSS 3 months, SSS 3 months, DML 1 and 3 months, and SPL 3 months, there were statistically significant changes better outcomes towards PRP injection group compared to the control group. Conclusion: PRP injections provided better short- to mid-term relief and improved electrophysiological outcomes compared to corticosteroid injections in mild to moderate CTS cases.